2016
DOI: 10.1007/s40273-016-0443-7
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Utility of Quadrivalent Versus Trivalent Influenza Vaccine in Germany, Using an Individual-Based Dynamic Transmission Model

Abstract: BackgroundSeasonal influenza infection is primarily caused by circulation of two influenza A strain subtypes and strains from two B lineages that vary each year. Trivalent influenza vaccine (TIV) contains only one of the two B-lineage strains, resulting in mismatches between vaccine strains and the predominant circulating B lineage. Quadrivalent influenza vaccine (QIV) includes both B-lineage strains. The objective was to estimate the cost-utility of introducing QIV to replace TIV in Germany.MethodsAn individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 24 publications
2
50
0
1
Order By: Relevance
“…Of these 35 studies, 2 studies were excluded after screening titles and abstracts, and from 18 studies no full-text was available as these referred to conference abstracts only. As one additional study that met our inclusion criteria was identified outside the initial search, we ended up with 16 eligible studies [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. The flowchart of the study identification process is displayed in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these 35 studies, 2 studies were excluded after screening titles and abstracts, and from 18 studies no full-text was available as these referred to conference abstracts only. As one additional study that met our inclusion criteria was identified outside the initial search, we ended up with 16 eligible studies [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. The flowchart of the study identification process is displayed in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
“…A total of 13 out of 16 studies were ranked as good, adhering to more than 17 out of 24 items on the CHEERs checklist [20][21][22][23][24][25][26][28][29][30][31]33,35], while 3 studies were assessed as moderate, adhering to less than 17 out of 24 points [27,32,34]. Arguments for the choice of time-horizon and model-type were most often not reported.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations